Diseño conceptual de un fotobiorreactor para la producción de hidrógeno (2022)
This research work generates a proposal for the sizing and planning of a photobioreactor for hydrogen production, because traditional methods produce large amounts of greenhouse gases, which have harmful consequences on the environment; and the production of hydrogen through bioreactors is a promising alternative with enormous potential. Initially, the design is proposed using microorganisms that have the property of producing hydrogen under specific conditions, therefore, an investigation and evaluation is made regarding the optimal microorganisms and it is determined that the Chlorella Vulgaris microalgae has a satisfactory operation and is chosen as the body to work.